Anterior, Posterior and Anterior–Posterior Approaches for the Treatment of Thoracolumbar Burst Fractures: A Network Meta-Analysis of Randomized Controlled Trials - Yuchen Duan; Dagang Feng; Jun Chen; Yamei Wu; Tong Li; Leiming Jiang; Yong Huang (Journal of Investigative Surgery)
Purpose To compare the clinical and radiological results of the anterior approach versus the posterior approach versus the anterior–posterior approach for the treatment of thoracolumbar burst fractures.Methods The network meta-analysis was performed in accordance with the PRISMA Statement. Electronic searches of PubMed and Embase were conducted up to June 22, 2023, for relevant randomized controlled trials. STATA13.0 was used to perform network meta-analysis. p < .05 was considered significant.Results Nine RCTs with a total of 550 patients receiving surgical treatment in at least two of the three approaches, including anterior, posterior and anterior–posterior approaches, were included. The surgical duration and intraoperative bleeding volume in the posterior approach were significantly lower than those in the anterior (SMD, −1.72; 95% CI, −2.82, −0.62) and anterior–posterior approaches (SMD, 3.33; 95% CI, 1.65, 5.00). The surgical duration in the anterior approach was significantly lower than that in the anterior–posterior approach (SMD, 1.61; 95% CI, 0.12, 3.10). The Cobb angle in the anterior–posterior approach was significantly lower than that in the anterior approach (MD, −4.83; 95% CI, −9.60, −0.05). The VAS score in the posterior approach was significantly higher than that in the anterior approach (MD, 0.85; 95% CI, 0.55, 1.16) and anterior–posterior approach (MD, −0.84; 95% CI, −1.12, −0.55). No significant difference was identified among the three surgical approaches in implant failure rate and infection rate.Conclusion All three approaches were safe approaches with advantages and disadvantages. The selection of surgical approaches for the treatment of thoracolumbar burst fractures may be individualized.